Deciphering the genetic landscape of tomato leaf curl New Delhi virus: Dynamic and region-specific diversity revealed by comprehensive sequence analyses - Zafar Iqbal; Adil Alshoaibi; Sallah Ahmad Al Hashedi; Muhammad Naeem Sattar; Khaled Muhammad Amin Ramadan (PLoS ONE, 2025)
Tomato leaf curl New Delhi virus (ToLCNDV), a swiftly spreading bipartite begomovirus infecting ~43 plant species across Asia, Africa, and Europe, poses a major agricultural threat. This study comprehensively investigated the genetic diversity and evolutionary dynamics of ToLCNDV using a large dataset of sequences from diverse geographic regions across Asia, Africa, and Europe. Phylogenetic analysis of DNA-A (TA) and DNA-B (TB) components revealed seven major clades for each component, demonstrating regional but not host-specific clustering. Notably, TA and TB exhibited distinct geographic segregation and genetic diversity, with cognate segments often clustering separately. Extensive recombination events were detected (44 in TA and 45 in TB), involving both intra- and interspecies events. While TA displayed higher overall genetic diversity indices, TB exhibited greater nucleotide diversity (π = 0.11%) compared to TA (π = 0.057%) and a slightly faster evolutionary rate (8.15 × 10‒04 substitutions/site/year vs. 7.25 × 10‒04 for TA). Demographic analysis indicated strong negative selection on both components (TA and TB) and their coding regions, albeit with varying intensity. India and Pakistan, known ToLCNDV hotspots, harbored the highest viral diversity and isolate numbers. This study highlights the complex interplay of genetic diversity, recombination, and selection in shaping ToLCNDV evolution, revealing distinct evolutionary trajectories for its genomic components and in different countries. These findings enhance understanding of ToLCNDV evolution and support informed control strategies.